Rancangan Simulasi Model Sistem Dinamis Pasok Kentang di Indonesia - Lolanda Hamim Annisa; Puspitasari, Wiji Tri (Journal of Agribusiness Science and Rural Development, 2024)
Potato supply chain system in this study comprises suppliers, producers, and consumers. Within the producer supply chain, potato production faces a deficit against domestic demand due to factors such as decreased productivity influenced by the type of seed used, rainfall, and harvesting processes. In this research, the Mean Absolute Percentage Error (MAPE) method is employed to assess the potato supply chain system for the next 10 years from social, economic, and environmental perspectives. This study combines explanatory and causal research, utilizing secondary data in the form of time series data. The simulation employs a suitable numerical integration method to achieve an accurate representation of processes within the system. Initialization considers the initial conditions and system parameters. Simulation results are analyzed to identify potential risks and opportunities that could impact potato supply availability. By utilizing this model, policies and strategies can be virtually tested to enhance national food security. Moreover, this simulation serves as an effective tool for designing contingency plans and mitigation measures to address various crisis scenarios that may arise in the potato supply chain, considering a productivity scenario increase from 16.56 tons/ha to 17.56 tons/ha.